Unraveling the patterns of small mammal species richness in the southernmost aridlands of South America - Formoso, Anahí Elizabeth; Teta, Pablo Vicente; Carbajo, Anibal Eduardo; Pardiñas, Ulises Francisco J. (Journal of Arid Environments)
Understanding the patterns of species richness is a critical aspect for the conservation of biodiversity. Patagonia is located southern of 40°S, mostly covered by an aridland and is the only area of the Southern Hemisphere (excluding Antarctica) that allows the study of a high-latitude terrestrial biota. In this work we describe the spatial variation of species richness of the non-flying small mammal assemblages, covering ∼12° of latitude in Patagonia. We analyzed 100,000 specimens and the relation between environmental variables and small mammal richness. Species richness decreased southwards and eastwards and turnover of species was not observed. We found high richness values in the north of Patagonia and high correlations between species richness and environmental variables in the south. We suggest that current species richness distribution in Patagonia is the result of historical (glacial history and main rivers acting as geographic barriers) and current climatic factors (e.g., temperature) along with species ecology. Our results highlight the importance of northern Patagonia as a reservoir of diversity across time and as most of the glacial refuges were potentially located on this area, we might expect it to be more severely impacted by current global warming. Fil: Formoso, Anahí Elizabeth. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Diversidad y Evolución Austral; Argentina Fil: Teta, Pablo Vicente. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Diversidad y Evolución Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales Argentina Fil: Carbajo, Anibal Eduardo. Universidad Nacional de San Martín. Instituto de Investigación e Ingeniería Ambiental; Argentina. Consejo Nacional de Investigaciones ...